Spectrophotometric Determination of Lamivudine in Pure and Tablet Forms - A. Biksham Babu; G. Ramu; Ch. Muralikrishna; S. Brahma Reddy; C. Rambabu (E-Journal of Chemistry)
Two visible spectrophotometric methods have been developed for the determination of Lamivudine(LMV) in pure and tablet forms. Method-A is based on oxidation of 3-methyl-2-benzathiazolinone hydrazone (MBTH) in the presence of iodoso benzene diacetate (IBDA) to form electrophilic intermediate which is an active coupling species that reacts with the coupler (LMV) by electrophillic attack on the most nucleophilic site on cyclic ring of the coupler. Method-B depends on diazonium salt formation and consequent reaction with resorcinol producing colored product. The absorbances are measured at 590 nm and 540 nm for Method-A and Method-B respectively. Beer's law is obeyed in the concentration range of 10.0-60.0 μg/mL for both the methods. The correlation coefficient which is very close to unity indicates that there is good correlation between concentration and absorbance. LOD, LOQ, confidence levels and relative standard deviation are calculated for the developed methods. The developed methods were successfully applied to tablet forms.